2016
DOI: 10.2106/jbjs.15.00658
|View full text |Cite
|
Sign up to set email alerts
|

The Readability of AAOS Patient Education Materials: Evaluating the Progress Since 2008

Abstract: Ensuring that online patient education materials are written at an appropriate reading grade level would be expected to improve physician-patient communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 15 publications
5
111
0
Order By: Relevance
“…Although readability of PM&R resources was lowest among the three groups, both websites used for comparison, the AAOS and AAFP, have undergone changes to their patient educational materials and shown improvement in their reading level since initial analyses of their readability . This suggests that it is feasible to improve and write educational patient materials on complex medical topics in a more accessible manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although readability of PM&R resources was lowest among the three groups, both websites used for comparison, the AAOS and AAFP, have undergone changes to their patient educational materials and shown improvement in their reading level since initial analyses of their readability . This suggests that it is feasible to improve and write educational patient materials on complex medical topics in a more accessible manner.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this cross‐sectional study was to provide an initial analysis of the readability of patient education materials provided by PM&R professional societies. A secondary objective was to compare the readability of PM&R patient education materials to two other frequently accessed sources of patient handouts, the American Academy of Orthopaedic Surgeons (AAOS) and the American Academy of Family Physicians (AAFP), which have been previously analyzed in terms of readability . Our hypothesis was that PM&R patient education resources would exceed the recommended reading level.…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms are based on the number of syllables per word, the number of words per sentence and the number of sentences per paragraph. Whereas other validated readability algorithms, including the SMOG (Simple Measure of Gobbledygook) Grade, Coleman–Liau Index and Gunning Fog Index, are used outside of medicine, the Flesch–Kincaid Grade Level and the Flesch Reading Ease have been most widely applied in the medical field (Roberts et al, ). The Kruskal–Wallis test was used for unpaired comparisons of utility and readability between the five articles.…”
Section: Methodsmentioning
confidence: 99%
“…These materials have been criticized for their low readability. Analyses of the readability of patient education materials on the American Academy of Orthopaedic Surgeons (AAOS) website in 2008 and 2014 showed that little progress had been made in lowering reading grade levels of the online materials (Badarudeen and Sabharwal, ; Roberts, Zhang, and Dyer, ). It is unclear whether algorithmically calculated readability scores correlate with patients' perceptions of the utility of online patient education materials.…”
Section: Introductionmentioning
confidence: 99%
“…Written educational material for patients, whether delivered printed or on websites has the common drawback of being written at relatively high levels of reading ability, and far above the recommended levels. 148 Such a high level requirement of understanding has implications for people with limited health literacy 149 which has been described as applying to almost 50% of the public. 150,151 Recommended strategies for people with low health literacy, besides using a reduced reading level of writing material, is to use videos as an adjunct to verbal narratives to increase understanding, as well as illustrated narratives with personal or third--person stories with corresponding illustrations.…”
Section: Use and Perceptions Of Different Learning Methodsmentioning
confidence: 99%